Trimethoprim/sulfamethoxazole-induced acute renal failure: A case report - Gabriella Nucera; Valentina Raffaelli; Lisa Caliari; Giulia Cantoni; Pietro Marino (Journal of Health and Social Sciences)
The patient was an 80-year-old man who arrived at the emergency room with breathing problems. He presented a history of chronic obstructive pulmonary disease (COPD), hypertension, diabetes mellitus and early (stage 1) chronic renal failure with normal levels of creatinine and no sign and symptoms of renal disease. A chest X-ray showed pneumonia. Therefore, he was first treated with 1 g daily of ceftriaxone IV. We did not observe any clinical improvement, and for this reason, a sputum culture was performed to guide the right antibiotic treatment. Subsequently, we started a new antibiotic therapy with trimethoprim/sulfamethoxazole (TMP/SMX) adjusted to renal functioning. Appropriate medical treatment was administered, as well as urine alkalinisation. After the first day of treatment, the patient’s clinical and laboratory status worsened very quickly, with an increased level of serum creatinine from 1.5 to 3.5 mg/dL. We stopped administering the antibiotic therapy immediately. However, we observed acute renal failure with a serum creatinine level of 9.0 mg/dL and four days after his admission, the patient died. Literature showed that patients can develop acute kidney injury (AKI) during or immediately following TMP/SMX therapy. Intrinsic renal impairment –rather, interstitial nephritis– appeared responsible for the great majority of cases, and impairment was transient if therapy was discontinued. In our study, despite the therapy with TMP/SMX was immediately discontinued, and our patient underwent appropriate medical treatment, urine alkalinisation and, then, haemodialysis, the AKI was rapidly fatal. In conclusion, particular attention should be paid to prescribing TMP/SMX to patients affected by chronic renal failure.